THE PURCHASING PROCESS AND THE CRITERIA FOR EVALUATING VENDORS ACCORDING TO FSSC 22000 VER 6.0 CONTRIBUTING TO THE GREEN FOOD ECONOMY - Huynh Kim Phung; Huynh Thi Thuy Loan; Ho Thi Ngoc Nhung; Lai Thi Hien; Nguyen Thi Thuy Duyen (HUIT Journal of Science, 2025)
This paper proposes a structured vendor selection process tailored for food processing factories, integrating both economic evaluation and food safety compliance in accordance with the FSSC 22000 Version 6.0 standard. The study contributes to the green food economy by ensuring that suppliers not only meet traditional criteria—such as pricing, delivery, and capacity—but also comply with food safety regulations and sustainability practices. A practical framework is developed, including a step-by-step purchasing process, risk-based evaluation forms, and scoring tables. Supplier assessment criteria are divided into two main categories: economic (e.g., cost, quality, delivery) and food safety (e.g., certification, traceability, food defense, internal audit). A hypothetical case study demonstrates the feasibility of the framework in selecting suitable suppliers. The proposed model enhances transparency, compliance, and consistency in procurement activities for food manufacturers.